2015
DOI: 10.1088/0022-3727/48/41/415102
|View full text |Cite
|
Sign up to set email alerts
|

Infrared dielectric functions and optical phonons of wurtzite YxAl1−xN (0  ⩽  x  ⩽  0.22)

Abstract: YAlN is a new member of the group-III nitride family with potential for applications in next generation piezoelectric and light emitting devices. In this work we report the infrared dielectric functions and optical phonons of wurtzite (0001) YxAl1-xN epitaxial films with 0 ≤ x ≤ 0.22.The films are grown by magnetron sputtering epitaxy on c-plane Al2O3 and their phonon properties are investigated using infrared spectroscopic ellipsometry and Raman scattering spectroscopy. The infrared-active E1(TO) and LO, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…In Figure 6d, the determined bandgap values are plotted versus the Y content determined by TOF-SIMS. The experimental values of the sputtered samples presented by Sedrine et al [40] are shown as well as the theoretical values of Ramírez-Montez et al, [30] who calculated the direct and indirect wurtzite and cubic bandgaps of AlYN over the whole composition range, concluding that both the binary rock salt compounds as well as wurtzite Al 0.25 Y 0.75 N and YN have an indirect bandgap. These calculations underestimate the experimental bandgap of wurtzite AlN by 0.815 eV.…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…In Figure 6d, the determined bandgap values are plotted versus the Y content determined by TOF-SIMS. The experimental values of the sputtered samples presented by Sedrine et al [40] are shown as well as the theoretical values of Ramírez-Montez et al, [30] who calculated the direct and indirect wurtzite and cubic bandgaps of AlYN over the whole composition range, concluding that both the binary rock salt compounds as well as wurtzite Al 0.25 Y 0.75 N and YN have an indirect bandgap. These calculations underestimate the experimental bandgap of wurtzite AlN by 0.815 eV.…”
Section: Resultssupporting
confidence: 61%
“…Different kinds of measurements were performed, such as phase analysis (2θ/θ-scan), azimuthal Φ-scan (e.g., to easily distinguish the presence of cubic inclusions), and pole figures (e.g., to estimate the presence of textures or twisting). While the AlYN layers deposited between 900 and 1000 °C showed typical wurtzite phase-related peaks (0002 peak at %35°-36°) and the cubic phase could not be detected, the layer grown at 1100 °C seemed to have traces of cubic phase inclusions, while the sample growth at 1200 °C was rich in cubic phase inclusions (100 peak at %31°-32°), [22,40] as visible in the Φ-scan (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Raman measurements were performed to support the IRSE measurements. For quantitative comparison of the DFs and Raman spectra, we calculate the imaginary part of the dielectric loss function (ω) from pbp-DFs [74]: In the range ω < 1000 cm −1 , the Raman spectra are dominated by phonons from the substrates, namely the TO( ) Si at 521 cm −1 , the TO( ) 3C−SiC at 795 cm −1 , and the LO( ) Si at 972 cm −1 [75]. The TO( ) c−GaN phonon mode is forbidden and therefore not visible in these Raman spectra [76,77].…”
Section: Table II Characterization Results Of the Investigated Samplmentioning
confidence: 99%
“…For the samples studied here, the optical axes of ZnO are oriented parallel to the surface normal. Therefore, no mode conversion of p-polarized light to s-polarized light and vice versa occurs and standard ellipsometry can be applied [18,34]. The SE spectra of all samples were analysed by using a 3-layer physical model consisting of a bulk ZnO substrate, a ZnO damaged layer and a surface roughness layer, as illustrated in Figure 5.…”
Section: Structural and Optical Damagementioning
confidence: 99%